A study on the falls factors among the older adult with cognitive impairment based on large-sample data - Wang, Changying; Zhang, Yunwei; Wang, Jin; Wan, Lingshan; Li, Bo; Ding, Hansheng (Frontiers in Public Health, 2024)
Introduction This study explored the correlative factors of falls among the older adult with cognitive impairment, to provide distinct evidence for preventing falls in the older adult with cognitive impairment compared with the general older adult population. Methods This study was based on a cross-sectional survey, with an older adult population of 124,124 was included. The data was sourced from the Elderly Care Unified Needs Assessment for Long-Term Care Insurance in Shanghai. Binary and multivariable logistic regression analyses were conducted sequentially on the correlative factors of falls. Multivariable logistic regression was performed on variables that were significant, stratified by cognitive function levels. Results The incidence of fall in the past 90 days was 17.67% in this study. Specific variables such as gender (male), advanced age (≥80), residence with a elevator (or lift), mild or moderate disability, quality of sleep (acceptable/poor) were negatively correlated with falls, while higher education level, living alone, residence with indoor steps, unclean and untidy living environment, MCI or dementia, chronic diseases, restricted joints, impaired vision, and the use of diaper were positively correlative factors of falls. Comparing with older adult with normal cognitive functions, older adult with dementia faced a higher risk of falling due to accessibility barrier in the residence. For general older adults, less frequency of going outside and poor social interactions were positively correlated with falls, while for older adult with cognitive impairments, going outside moderately (sometimes) was found positively correlated with falls. Older adults with cognitive impairments have increased fall risks associated with chronic diseases, restricted joints, and the use of diaper. The risk of falling escalated with the greater number of chronic diseases. Discussion For older adult with cognitive impairments, it is advisable to live with others. Additionally, creating an accessible living environment and maintaining the cleanness and tidiness can effectively reduce the risk of falls, particularly for those with MCI or dementia. Optimal outdoor activity plans should be developed separately based on the cognitive function of older adults. Older adult with dementia who have comorbidities should be paid special attention in fall prevention compared to the general older adult population.